Post-Brexit Identity Crisis: The African -Asian Communities - Kheliel, Attik, Sekoura Souheila (University of El-oued, 2022)
تسعى هذه المذكرة إلى البحث في الحدث الأبرز الذي شهدته المملكة المتحدة، وهو خروجها من الاتحاد الأوروبي، والدوافع التي أدت بها إلى الانشقاق عنه، وتأثيره عليها. كما تبحث بشكل أدق في بعض التحديات التي أثارها هذا الخروج، جنبًا إلى جنب مع إرث بريطانيا من العنصرية في خلق أزمة هوية للمجتمعات الأفريقية الآسيوية القاطنين فيها. ومن ثم تحاول الدراسة الإجابة على السؤال التالي: كيف أثر خروج بريطانيا من الاتحاد الأوروبي على الإحساس بالهوية لدى المجتمعات الأفريقية والآسيوية؟ وسعيا للتوصل إلى إجابة مناسبة لإشكالية البحث، تتبنى الدراسة المقاربة النوعية، وتستخدم المنهج التاريخي التحليلي، وكذلك المنهج الوصفي التحليلي في جمع وتحليل البيانات من المقالات العلمية والصحفية والكتب. وقد كشفت الدراسة أن مساهمة استفتاء الخروج من الاتحاد الأوروبي في تصاعد العنصرية وجرائم الكراهية ضد المهاجرين هو مجرد تذكير بتاريخ بريطانيا مع العنصرية وعدم المساواة. وأن خروجها قد جلب العديد من التحديات التي أثرت سلبًا على الهوية الأفريقية الآسيوية.. The dissertation investigates the most prominent event the UK witnessed namely Brexit, its driving forces and its impact on the UK in general. In deeper, the study investigates some of the challenges brought by Brexit and how these obstacles alongside Britain's legacy of racism have contributed to creating an identity crisis for the African-Asian communities. Thus, the study tries to answer the question of how Brexit has affected the African-Asian sense of identity. To come up with an appropriate answer to the research questions the study adopted a qualitative approach and used the analytical historical method and descriptive analytical method as well in collecting and analysing data from scholarly and newspaper articles and books. The study reveals that the European Union referendum's contribution to the rise of racism and hate crimes against immigrants was just a reminder of Britain's history with racism and inequality. It also shows that Brexit has brought many challenges that negatively affected African-Asian identity. Keywords: African-Asian communities, Brexit, European Union Referendum, Identity crisis, Immigrants
Keywords: أزمة الهوية، استفتاء الاتحاد الأوروبي، خروج بريطانيا من الاتحاد الأوروبي، المجتمعات الأفريقية الآسيوية، المهاجرين.; Identity crisis, EU referendum, Brexit, Afro-Asian communities, immigrants.